Field-effect based chemical and biological sensing : theory and implementation - Kaisti, Matti (fi=Turun yliopisto|en=University of Turku|, 2017)
Electrochemical sensors share many properties of an ideal (bio)chemical sensor. They can be easily miniaturized with high parallel sensing capabilities,with rugged structure and at low cost. The response obtained from thetarget analyte is directly in electrical form allowing convenient data post-processing and simple interfacing to standard electrical components. With ﬁeld-eﬀect transistor (FET) based sensors, the transducing principle relies on direct detection of interfacial charge allowing detection of various ions and charged macromolecules. This thesis investigates FET based sensors for biological and chemical sensing. First, an ion-sensitive ﬂoating gate FET (ISFGFET) structure is studied and modeled. The proposed model reveals novel abilities of the structure not found in conventional ion-sensitive FETs (ISFETs). With IS-FGFET, we can simultaneously optimize the transistor operating point and modulate the charging of the surface and the ionic screening layer via the ﬁeld eﬀect. This control is predicted to allow reduced electric double layer screening as well as the possibility to enhance charged molecule attachment to the sensing surface. The model can predict sensor characteristic curves in pH sensing in absolute terms and allows any potential to be computed in the sensor including the electrical part and the electrolyte solution. Furthermore, a compact ISFGFET variant is merged into electric circuit simulator, which allows it to be simulated as a standard electrical component with electrical simulations tools of high computational eﬃciency, and allows simple modiﬁcations such as addition of parasitic elements, temperature eﬀects, or even temporal drifts. Next, another transistor based conﬁguration, the extended-gate ISFET is studied. The simplicity of the proposed conﬁguration allows a universal potentiometric approach where a wide variety of chemical and biological sensors can be constructed. The design philosophy for this sensing structure is to use the shelf electric components and standard electric manufacturing processes. Such an extended-gate structure is beneﬁcial since the dry electronics can be completely separated from the wet sensing environment. The extended-gate allows simple functionalization towards chemical and biological sensing. A proof-of-concept of this structure was veriﬁed through organo modiﬁed gold platforms with ion-selective membranes. A comparison with standard open-circuit potentiometry reveals that the sensing elements in a disposable sensing platform arrays provide comparable performance to traditional electrodes. Finally, a universal battery operated hand-held electrical readout device is designed for multiplexed detection of the disposable sensors with wireless smartphone data plotting, control, and storage. Organic polymers play an important role in the interfacial properties of sensors studied in this thesis. The polymer coating is attractive in chemical sensing because of its redox sensitivity, bio-immobilization capability, ion-to-electron transducing capability, and applicability, for example via a simple low-cost drop-casting. This structure simpliﬁes the design of the sensor substantially and the coating increases the amount of possible target applications.